Linking a transport dynamic model with an emissions model to aid air pollution evaluations of transport policies in Latin America. Issue 3 (3rd July 2017) - Guzman, Luis A.; Orjuela, Juan Pablo
ABSTRACT: Considering the key role of the transport sector in the economy and its contribution to greenhouse gas (GHG) and local air pollutant emissions, the development of integrated techniques to evaluate long-term urban trends should be a top priority for creating a more sustainable society. This paper presents an integrated model for reliable estimation of passenger transport emissions of local pollutants and CO2 using an integrated Land-Use and Transport Interaction (LUTI) model in Bogota (Colombia) between 2010 and 2026. Two additional scenarios are modelled to illustrate the use of the model to evaluate the impacts of possible policy interventions. An alternative system dynamics approach is proposed as part of a structured decision-making process. The methodology uses causal loop diagrams (CLD) from systems dynamics to explain cause-and-effect relations, through linking the transport emissions and transport subsystems. The emissions model considers 11 different vehicle categories in total and emission factors for CO2, NO x, THC and PM2.5 were established using local data collected with portable devices and from other available secondary sources. Adjustment factors were established in order to account for ageing of vehicles, technology improvements and changes in category distributions. The development of a general framework based on dynamic systems for assessing long-term emissions estimations according with the particular transport systems is needed for effective sustainable transport planning. The inclusion of adjustment factors for ageing and technology changes provides more reliable projections and helps identify important long-term trends in the emissions inventory. The scenarios proposed are meant to show the results obtained by the model to assist the decision-making process and do not represent current measures in the city or the best practices available. Due to an increase in the use of the private car transport, CO2 emissions will continue to grow in Bogota despite possible technology improvements. Results show that the use of natural gas in the public transport fleet would imply considerable emission reductions in all studied species, being this an alternative technology while electric buses become financially viable.